Design and Development of Fan Speed and Light Speed Control Systems with Android-Based Voice Commands - Anna Nur Nazilah Chamim; Rama Okta Wiyagi; Karisma Trinanda Putra; Faruliyan Arya Ferisnanda; Yessi Jusman (Journal of Electrical Technology UMY, 2018)
At this time controlling electrical equipment in the form of fans and lights are still mostly using conventional switches. By using an android voice command device with a bluetooth connection, controlling the equipment can be easier. Using a Bluetooth connection will reduce the use of cables and speed up the process of activating or deactivating electronic devices because they do not have to get close to reach the switch. With input in the form of voice commands is very easy in controlling electronic devices such as fans and lights. With the adjustment of the fan speed and brightness of the lights with voice commands can save electricity and more easily in its settings